Concurrent squamous cell carcinoma and warthin tumor - A rare encounter - Sakshi Deorah; Shivanjali Raghuvanshi; Sharon John; Krachi Agarwal; Shalini Gupta (Oral Oncology Reports)
Oral cancer ranks sixth most common malignant neoplasm worldwide, with Squamous Cell Carcinoma being the predominant type observed in the head and neck region. Smoking and tobacco chewing are the two prime aetiological factors. Oral squamous cell carcinomas (OSCC) and Warthin tumors (WT) are commonly observed lesions in individuals with head and neck tumors. Nevertheless, the simultaneous occurrence of these two tumors is an infrequent event. WT, also known as papillary cystadenoma lymphomatosum is a benign tumor of the salivary gland. Malignant transformation in this tumor is mostly seen in the lymphoid component. This case report details the experience of a 68-year-old patient diagnosed with OSCC on the left lateral border of the tongue, who underwent extensive surgical procedures, including selective neck dissection. Unexpectedly, the histopathological analysis of the neck dissection revealed the presence of a WT in the left submandibular gland. Due to the proximity of nearby lymph nodes, it can lead to a misdiagnosis of metastasis in individuals diagnosed with head and neck cancer. Hence, we present a case involving a multicentric Warthin tumor in the submandibular region, which mimicked lymph node metastasis from OSCC in the corresponding oral region.